Measurement of long‐term iron absorption and loss during iron supplementation using a stable isotope of iron (57Fe). (30th August 2020) - Speich, Cornelia; Wegmüller, Rita; Brittenham, Gary M.; Zeder, Christophe; Cercamondi, Colin I.; Buhl, Daniela; Prentice, Andrew M.; Zimmermann, Michael B.; Moretti, Diego
Summary: We report the first measurements of long‐term iron absorption and loss during iron supplementation in African children using a stable isotope of iron ( 57 Fe). After uniform labelling of body iron with 57 Fe, iron absorption is proportional to the rate of decrease in the 57 Fe tracer concentration, while iron loss is proportional to the rate of decrease in the 57 Fe tracer amount. Anaemic Gambian toddlers were given 2 mg 57 Fe orally to equilibrate with total body iron over 8–11 months. After assignment to the positive control arm of the HIGH study, 22 toddlers consumed a micronutrient powder containing 12 mg iron for 12 weeks followed by 12 weeks without iron supplementation. Their daily iron absorption increased 3·8‐fold during the iron supplementation period compared to the control period [median (interquartile range, IQR): 1·00 (0·82; 1·28) mg/day vs. 0·26 (0·22; 0·35) mg/day; P = 0·001]. Unexpectedly, during the supplementation period, daily iron loss also increased by 3·4‐fold [0·75 (0·55; 0·87) mg/day vs. 0·22 (0·19; 0·29) mg/day; P = 0·005]. Consequently, most ( 72%) of the absorbed iron was lost during supplementation. Long‐term studies of iron absorption and loss are a promising and accurate method for assessing and quantifying long‐term iron balance and may provide a reference method for evaluating iron intervention programs in vulnerable population groups. This study was registered as ISRCTN 0720906.